Efficient Solid‐State Photoluminescence of Graphene Quantum Dots Embedded in Boron Oxynitride for AC‐Electroluminescent Device. Issue 38 (7th August 2018) - Park, Minsu; Yoon, Hyewon; Lee, Jaeho; Kim, Jungmo; Lee, Jinho; Lee, Seong‐Eui; Yoo, Seunghyup; Jeon, Seokwoo
Abstract: Emerging graphene quantum dots (GQDs) have received much attention for use as next‐generation light‐emitting diodes. However, in the solid‐state, π‐interaction‐induced aggregation‐caused photoluminescence (PL) quenching (ACQ) in GQDs makes it challenging to realize high‐performance devices. Herein, GQDs incorporated with boron oxynitride (GQD@BNO) are prepared from a mixture of GQDs, boric acid, and urea in water via one‐step microwave heating. Due to the effective dispersion in the BNO matrix, ACQ is significantly suppressed, resulting in high PL quantum yields (PL‐QYs) of up to 36.4%, eightfold higher than that of pristine GQD in water. The PL‐QY enhancement results from an increase in the spontaneous emission rate of GQDs due to the surrounding BNO matrix, which provides a high‐refractive‐index material and fluorescence energy transfer from the larger‐gap BNO donor to the smaller‐gap GQD acceptor. A high solid‐state PL‐QY makes the GQD@BNO an ideal active material for use in AC powder electroluminescent (ACPEL) devices, with the luminance of the first working GQD‐based ACPEL device exceeding 283 cd m −2 . This successful demonstration shows promise for the use of GQDs in the field of low‐cost, ecofriendly electroluminescent devices. Abstract : Efficient solid‐state photoluminescent graphene quantum dots embedded in boron oxynitride (GQD@BNO) are synthesized via simple microwave heating. The GQD@BNO shows high photoluminescence quantum yields of up to 36.4%, enabling successful demonstration of the first ever GQD‐based alternating‐current powder electroluminescent device with a high luminance exceeding 283 cd m −2 .